“I Want to Withdraw My Hibah”: Why and How to Explain it? - Mohd Khairy Kamarudin; Nasrul Hisyam Nor Muhamad; Suhaili Alma'amun; Norhaifa Ganti (Journal of Islamic Thought and Civilization, 2022)
Hibah or Islamic inter-vivos plays a vital role in reducing unclaimed inheritance estate problems, aiding recipients, and expecting recipients’ care. However, there are cases of withdrawn hibah that have been argued in the court. This study was performed to understand this problem by interviewing hibah experts in Malaysia. Thematic analysis was applied to find an overview of why donors withdraw their hibah by interviewing 19 respondents who are hibah experts in Malaysia. There were two main themes which were ‘Donor’s desire’ and ‘Recipient’s attitude.’ ‘Donor’s desire’ can be understood by the desire of donor to get benefits from the property that has been perfectly transferred or if the donor still resides on the property. Meanwhile, ‘Recipient’s attitude’ describes a change in recipients’ attitude such as ignoring and expelling the donors from the transferred property. The recipients also might sell the transferred property. This reason leads to donors wanting to withdraw their hibah. This study’s findings recommend that absolute hibah needs to be replaced with hibah legal documentation or living trust. These types of hibah are recognized by Sharī‘ah and Civil law and enable the donors to withdraw their hibah during lifetime. This study is the first attempt to discuss profoundly withdrawn hibah in qualitative approach. The paper offers an additional study on hibah practice in Malaysia.Keywords: Thematic analysis, Hibah, Islamic inheritance, Inter-vivos, Withdrawn hibah.